Prospective of low dose naltrexone use in treatment of autoimmune pathology and endometriosis - O. V. Golianovskyi; O. O. Andrienko; O. V. Furman; Phil Boyle (Publishing House TRILIST, 2020)
There are still many complex issues in the management of autoimmune pathologies in gynecology and reproductology, endometriosis in particular. Naltrexone, a competitive antagonist of opiate receptors in the central and peripheral nervous systems, reveals new qualities such as effects on autoimmune processes. Naltrexone in low doses of 1.7-5 mg (Low Dose Naltrexone, LDN) revealed the opposite effect on opiate receptors in the form of a rebound effect and, as a consequence, a strong increase in endogenous endorphins and enkephalins. Studies of elevated levels of these neurotransmitters have provided evidence of a multidisciplinary beneficial effect on the immune system of people with endorphin and enkephalin deficiency, an association between the endogenous opiate system and cells and tissue growth in general and healthy immune function was confirmed. The most explored effects of them are such as blocking the synthesis of pro inflammatory cytokines IL-6, IL-12, tumor necrosis factor, the effect on neuroglia through toll-like receptors, the effect on the cycle cells growth, especially malignant tumor cells, through interaction with opiate growth factor, modulation synthesis of T- and B-lymphocytes. Growing evidence of LDN efficacy is becoming a potentially effective clinical practice in autoimmune pathologies, but still off-label used. Some data of clinical trials is presented. Four studies with Crohn's disease with results of relief of symptoms and remission, including experience in pediatrics. Three clinical trials with LDN results in multiple sclerosis with improved quality of life and improved symptoms. The scientific hypothesis suggests the success of LDN due to the reduction of induced nitric oxide synthase activity. The success of management of patients with malignant tumors is also presented. The article contains the latest data from clinical trials on reported serious and non-serious side effects of naltrexone at various doses, including data confirming the safety of taking mid-therapeutic naltrexone doses throughout pregnancy. These effects of LDN may prove to be effective in management patients with endometriosis.